Barriers and Challenges in Seeking Healthcare by Pediatric Tuberculosis Patients Attending DOTS Centers in Urban Areas of Delhi - Sunita Dhaked; Nandini Sharma; K.K. Chopra; Ashwani Khanna (MAMC Journal of Medical Sciences, 2019)
Background: Healthcare seeking by pediatric tuberculosis (TB) patients is complicated because of some factors such as lack of knowledge among family members, diagnostic difficulties, limited resources, and treatment challenges. Aims: The aim of this article is to identify the barriers and challenges related to seeking healthcare by pediatric TB patients. Settings and Design: It was a prospective observational study conducted from January 2015 to December 2015 at two chest clinics. Materials and Methods: A predesigned, pretested, and semi-structured questionnaire was used to interview caregivers of pediatric TB patients and followed up at two more occasions, that is, at the end of intensive and of continuation phase, to identify the challenges they were facing during treatment. Statistical Analysis: Data were analyzed using SPSS software version 17 (SPSS Inc., New Delhi, Delhi, India) and P value less than 0.05 was considered significant. Result: The lack of knowledge was a barrier to understand the disease, seeking care, and being compliant with treatment as nearly 40% (41.8%) did not know that TB is infectious and more than half (55.3%) did not know that TB can occur in any age group. Only 14.2% knew about vaccine for TB, but no one had knowledge about isoniazid prophylaxis. Reported challenges in treatment seeking were high transport cost, long distance for higher government facility (83.7%), and interference with daily routine (39.0%), and in-treatment compliance were heavy pill burden (80%), refusal of child to take medicines (41.8%), fear of side effects (71.6%), and difficulty in powdering the medicines (35.5%). Conclusion: Major barrier was lack of knowledge about childhood TB and major challenge was heavy pill burden, which affected the compliance.